2012
DOI: 10.1016/j.bbrc.2011.11.060
|View full text |Cite
|
Sign up to set email alerts
|

Flaviviral helicase: Insights into the mechanism of action of a motor protein

Abstract: a b s t r a c tMotor proteins are involved in crucial cell activities, such as cargo transport or nucleic acid remodeling, by converting the free energy of ATP hydrolysis into motion or mechanical work. Flavivirus helicase is a motor protein involved in dsRNA separation during viral replication, thus essential for virus infection. Since a clear vision of the protein activity, in particular of the relationship between ATP cycling and dynamics, is missing, we carried over a molecular dynamics study on Dengue vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 15 publications
(28 reference statements)
0
20
0
Order By: Relevance
“…Structures displaying similar closed and open conformations of the apo-NS3 enzyme from HCV have also been reported, albeit from NS3 belonging to different HCV genotypes (25,(63)(64)(65). Recent molecular dynamics simulations indicated that DENV apo-NS3h also appears to oscillate between open and closed conformations (66), again suggesting an intrinsically dynamic behavior, although the structures of the apo-form of the enzyme in different conformations are not available. SAXS analyses of HCV and flavivirus NS3h in the presence or absence of an ATP analog might provide useful comparative information.…”
Section: Discussionmentioning
confidence: 82%
“…Structures displaying similar closed and open conformations of the apo-NS3 enzyme from HCV have also been reported, albeit from NS3 belonging to different HCV genotypes (25,(63)(64)(65). Recent molecular dynamics simulations indicated that DENV apo-NS3h also appears to oscillate between open and closed conformations (66), again suggesting an intrinsically dynamic behavior, although the structures of the apo-form of the enzyme in different conformations are not available. SAXS analyses of HCV and flavivirus NS3h in the presence or absence of an ATP analog might provide useful comparative information.…”
Section: Discussionmentioning
confidence: 82%
“…The flaviviral helicase belongs to the helicase superfamily 2 (SF2) and is located at the C-terminal domain of NS3 (REFS 152,153). NS3 is responsible for unwinding viral RNA during replication, and its activity is driven by an intrinsic NTPase activity 152,153 . The structure of NS3 helicase has been elucidated for many flaviviruses 154 , including ZIKV 155 .…”
Section: Target Assaysmentioning
confidence: 99%
“…The order of RNA capping has not been completely defined for flaviviruses, but the canonical Ping‐Pong mechanism for cap formation appears to be the most likely scenario (Figure ). The RNA triphosphatase is located in the NS3 helicase domain, and the RNA triphosphatase appears to overlap with the NTPase active site that powers the helicase . Newly synthesized negative and positive strand RNAs are triphosphorylated and would be appropriate substrates for the RNA triphosphatase.…”
Section: Rna Capping In Flavivirus Rna Replicationmentioning
confidence: 99%